Study of the effect of covolumes in BKW equation of state on detonation properties of CHNO explosives - Suceska, Muhamed (2013)
Due to its simplicity, the Becker-Kistiakowsky-Wilson (BKW) equation of state has been used in many thermochemical codes in the calculation of detonation properties. Much work has been done in the calibration of the BKW EOS parameters to achieve agreement with experimental detonation velocities and pressures thus resulting in many different sets of BKW constants (α, β, κ and θ) and covolumes of detonation products, with varying levels of accuracy over broad density limits, i.e. broad pressure limits. The covolumes of the product gases in BKW EOS may be regarded as measures of intermolecular interactions, and their values should affect the predicted detonation properties, particularly at higher explosives densities. This work aims to study the effect of covolumes on calculated values of detonation parameters. Several sets of covolumes available from literature and derived by different methods (matching experimental Hugoniots of individual products, by stochastic optimization, and calculated from van der Waals radii), were studied. In addition, the covolumes of the product gases were also calculated by ab initio methods. The effect of covolumes is studied comparing detonation properties calculated using different sets of covolumes, and experimental data for a series of standard CHNO explosives. It was found that it is possible to reproduce experimental detonation velocities and pressures within reasonable accuracy (root mean square error of less than 5 % for all tested sets) using different set of covolumes, and simultaneously optimizing constants in BKW EOS. However, different values of covolumes strongly affect the composition of detonation products at the Chapman-Jouguet state. It particularly applies to oxygen-deficient explosives and at higher densities, where formic acid appears to be an important detonation product.